DIVINE GUIDANCE AND AWARENESS: UNDERSTANDING FAMILY PLANNING PROGRAMS AMONG THE PUBLIC IN PAKISTAN - Muhammad Ibrar; Zuhaib Ali; Kamran Naeem; Ihsan Jamil; Muhammad Waseem (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Sacred Understanding: Evaluating the Community's Perception and Awareness of Family Planning Program in Three Villages of District Malakand, Pakistan. The study conducted among 169 married males in these villages revealed that family planning is not only beneficial for the society but also aligns with the religious teachings of spacing/gaps between children. The findings further emphasized the positive impact of family planning on the health of children and mothers, a value upheld in Islamic beliefs. The study suggests involving religious leaders in awareness programs to strengthen their effectiveness and ensure the program's continued success, ultimately contributing to the betterment of society and the fulfillment of religious duties.